Peginterferon Alfa-2a plus Ribavirin for Chronic Hepatitis C Virus Infection in HIV-Infected Patients - Torriani, Francesca J; Rodriguez-Torres, Maribel; Rockstroh, Jürgen K; Lissen, Eduardo; Gonzalez-García, Juan; Lazzarin, Adriano; Carosi, Giampiero; Sasadeusz, Joseph; Katlama, Christine; Montaner, Julio; Sette, Hoel; Passe, Sharon; et al. (The New England journal of medicine, 2004)
In this randomized trial involving patients with chronic hepatitis C who were also infected with the human immunodeficiency virus (HIV), peginterferon alfa-2a plus ribavirin was more effective than interferon alfa-2a plus ribavirin or peginterferon alfa-2a plus placebo (rates of sustained virologic response, 40 percent, 12 percent, and 20 percent, respectively). The rates of response were not as high as in previous studies involving HIV-negative patients. Potent antiretroviral therapy has reduced the morbidity and mortality associated with untreated human immunodeficiency virus (HIV) infection. 1 , 2 At the same time, the pattern of morbidity and mortality among HIV-infected persons has shifted, and clinicians responsible for the care of HIV-infected persons have been confronted with new challenges. Complications associated with concurrent hepatitis C virus (HCV) infection have emerged as one of the most frequent and complex issues in the care of patients with HIV infection and the acquired immunodeficiency syndrome (AIDS). 3 , 4 The current standard of care for chronic infection with HCV in persons without other infections is pegylated . . .